The impact of combined administration of paraquat and maneb on motor and non-motor functions in the rat. (17th December 2015) - Tinakoua, A.; Bouabid, S.; Faggiani, E.; De Deurwaerdère, P.; Lakhdar-Ghazal, N.; Benazzouz, A.
Highlights: Combined paraquat and maneb intoxication induced partial depletion de dopamine. Paraquat and maneb did not alter the content of norepinephrine and serotonin. Paraquat and maneb induced changes in the pattern of subthalamic nucleus neurons. Individuals are not equally sensitive to combined paraquat and maneb intoxication. Paraquat and maneb induced non-motor behaviors in rats without motor deficits. Abstract: Paraquat (PQ) and maneb (MB) are potential risk factors for Parkinson's disease. However, their impact on non-motor disorders, monoamine neurotransmission and basal ganglia function is not clearly determined. Here we investigated the effects of combined treatment with PQ/MB on motor behavior, anxiety and "depressive-like" disorders, tissue content of monoamines, and subthalamic nucleus (STN) neuronal activity. Male Sprague–Dawley rats were intoxicated by PQ (10 mg/kg) and MB (30 mg/kg) twice a week. Two weeks later, the majority of animals (group 1, 16/26) showed a severe loss of body weight with tremor and respiratory distress and others (group 2, 6/26) showed only tremor. Animals of group 2 received PQ/MB during four weeks before developing weight loss. A last group (group 3, 4/26) was insensitive to PQ/MB after 6 weeks of injections. Groups 1 and 2 displayed a failure of motor activity and motor coordination. Group 3 showed slight motor deficits only after the last injection of PQ/MB. Moreover, PQ/MB induced anxiety and "depressive-like" behaviors in animals of groups 2 and 3. Biochemical analysis showed that PQ/MB reduced striatal dopamine (DA) tissue content paralleled by changes in the activity of STN neurons without changing the content of norepinephrine and serotonin in the cortex. Our data provide evidence that individuals are not equally sensitive to PQ/MB and show that the motor deficits in vulnerable animals, are not only a result of DA neuron degeneration, but may also be a consequence of peripheral disabilities. Nevertheless, the parkinsonian-like non-motor impairments may be a direct consequence of the bilateral DA depletion.